Utilização de estatística descritiva para caracterização de variáveis em uma turma 5º ano no município de Moju-PA - OLIVEIRA, Welison da Conceição (2023)
Statistics guides teachers towards pedagogical reflections on factors present inside and outside the classroom, through quantitative and qualitative analyzes of these factors and their effects on student performance. This work is directed to the practical use of descriptive statistics applied to education. The identification of variables helps educational decisions and combats factors that hinder teaching and learning. The objective of this study was to characterize statistical variables, presenting basic mathematical parameters and measures of central tendency and dispersion that can be collected in the classroom. These variables, properly applied, tend to help teachers in actions to maximize learning and minimize teaching-learning barriers in the classroom.